A novel ketone diet enhances physical and cognitive performance - Murray, Andrew J.; Knight, Nicholas S.; Cole, Mark A.; Cochlin, Lowri E.; Carter, Emma; Tchabanenko, Kirill; Pichulik, Tica; Gulston, Melanie K.; Atherton, Helen J.; Schroeder, Marie A.; Deacon, Robert M. J.; Kashiwaya, Yoshihiro; et al. (Federation of American Society of Experimental Biology, 2016)
Ketone bodies are the most energy efficient fuel, yielding more ATP per mole of substrate than pyruvate and increasing the free energy released from ATP hydrolysis. Elevation of circulating ketones via high-fat, low-carbohydrate diets has been used for the treatment of drug-refractory epilepsy and for neurodegenerative diseases, such as Parkinson’s disease. Ketones may also be beneficial for muscle and brain in times of stress, such as endurance exercise. The challenge has been to raise circulating ketone levels using a palatable diet without altering lipid levels. We found that blood ketone levels can be increased, and cholesterol and triglycerides decreased, by feeding rats a novel ketone ester diet; chow supplemented with (R)-3-hydroxybutyl (R)-3-hydroxybutyrate as 30% of calories. For five days, rats on the ketone diet ran 32% further on a treadmill than control rats eating an isocaloric diet supplemented with either corn starch or palm oil (p<0.05). Ketone-fed rats completed an eight-arm radial maze test 38% faster than those on the other diets, making more correct decisions before making a mistake (p<0.05). Isolated, perfused hearts from rats fed the ketone diet had greater free energy available from ATP hydrolysis during increased work than hearts from rats on the other diets, as shown using 31P-NMR spectroscopy. The novel ketone diet therefore improved physical performance and cognitive function in rats, and its energy-sparing properties suggest that it may help to treat a range of human conditions with metabolic abnormalities.